THE LAW OF BUYING AND SELLING COFFEE GAYO WITH BA'I BITSAMANI'AJIL SYSTEM: Study of Fatwa DSN No.110/DSN-MUI/IX/2017 - Linda Fitriani (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
This article aims to investigate how Islamic law perceives the sale and purchase of coffee using the ba'i bitsamani'ajil system in Celala District, Central Aceh Regency. This research uses the type of field research (field research). The data collection techniques in this study are: Observations and interviews conducted with toke/agents (coffee buyers) and farmers (coffee sellers). Sources of information from primary data obtained from sellers and farmers/buyers. In contrast, secondary data is obtained from archival documents, articles, books and other sources that have been published to gain knowledge and can achieve valid results. The results of research on buying and selling coffee using the ba'i bitsamani'ajil system in Celala District, Central Aceh Regency, conducted by local residents, indicate that several factors encourage payment with the ba'i bitsamani'ajil system or deferral. The second factor is the buyer's (collector) desire for coffee, where some of the funds are not yet available on that day. However, in this case, it was discovered that some buyers failed to pay according to the initial agreement. In Islamic law, the practice of buying and selling coffee beans with payment through the ba'i bitsaman ajil system has fulfilled the pillars and conditions of bai' bitsaman ajil, which have been regulated in shara' (Islamic law). Still, it can turn invalid if, in practice, it is not fulfilled (denied) when the agreement has not been completed and can harm fellow parties, as explained in QS. An-Nisa': 29, which explains that it is forbidden to eat wealth, seeking wealth through means that Sharia does not justify